Agama Hindu di Indonesia: Perumusan Konsep Keberagamaan Hindu dalam Kehidupan Berbangsa dan Bernegara - Putu Eka Sura Adnyana; Ni Nyoman Suryani (Sanjiwani: Jurnal Filsafat, 2021)
Indian culture has a lot of influence on the religious and social activities of the Hindu community in the archipelago. One of them is the use of animals in the religious social activities of the Hindu community in the archipelago. The similarity of the concept of Vedic teachings and their implementation in the Land of the Archipelago encouraged the ancestors to fight for Hinduism to be recognized in Indonesia. This paper aims to describe and explain the journey of the formulation of Hinduism in Indonesia. This paper is expected to be useful for the wider community, especially the Hindu community. This paper uses the method of collecting data through observation, with a combination of listening and note-taking methods, as well as data analysis using qualitative descriptive analysis techniques and methods of presenting results with non-formal techniques. The syncretism of Vedic teachings and ancestral teachings has occurred for centuries, both from the 5 theories of the entry of Hinduism to Indonesia, from the process of the Indians traveling to the archipelago known as the Bali Yatra, and from the mangjawaken byasa mata process carried out by the king of Kediri, namely Dharma Wangsa. Firm in the 9th century AD. The recognition of Hinduism in Indonesia encouraged Hindu intellectuals at that time to immediately formulate Hindu religious concepts for the life of the nation and state, such as the name of the highest entity, the concept of carrying out daily prayers, holy days, organizations, and so on. This indicates the importance of understanding the Hindu red coat in Indonesia.